2016
DOI: 10.1155/2016/5816974
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Water Technology for Enhanced Extraction of Biochemical Compounds fromChlorella vulgaris

Abstract: Subcritical water extraction (SWE) technology has been used for the extraction of active compounds from different biomass materials with low process cost, mild operating conditions, short process times, and environmental sustainability. With the limited application of the technology to microalgal biomass, this work investigates parametrically the potential of subcritical water for high-yield extraction of biochemicals such as carbohydrates and proteins from microalgal biomass. The SWE process was optimized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 32 publications
3
22
0
1
Order By: Relevance
“…Several studies have reported that the effect of biomass loading is less significant when compared to temperature and reaction time 33) 34) . Awaluddin et al (2016) 35) have shown similar trends in their study.…”
Section: Lignin Puritysupporting
confidence: 80%
“…Several studies have reported that the effect of biomass loading is less significant when compared to temperature and reaction time 33) 34) . Awaluddin et al (2016) 35) have shown similar trends in their study.…”
Section: Lignin Puritysupporting
confidence: 80%
“…The main parameters that affect the extraction yield and the composition of the extract in SWE are the temperature, the extraction time, the biomass loading and the particle size. Some of the works that apply SWE for the extraction of microalgal carbohydrates evaluate the effect of these extraction parameters [34,35]. The results of these studies showed that the polysaccharide content on the final extract is greatly affected by the temperature.…”
Section: Pressurized Liquid Extraction For Microalgal Carbohydrates Ementioning
confidence: 99%
“…However, at higher temperature, the carbohydrate extraction yield decreases due to the degradation of the polysaccharides and besides, to the lower contribution of the reduction effect of the subcritical water dielectric constant. Apart from high temperatures, Awaluddin et al showed that long extraction times and high biomass loading negatively affected the carbohydrate recovery [35]. In other studies, the effect of SWE conditions was also evaluated in terms of chemical composition and bioactivity of the obtained extracts.…”
Section: Pressurized Liquid Extraction For Microalgal Carbohydrates Ementioning
confidence: 99%
“…It was determined that a temperature of 175 °C is adequate for extraction of phenols from Chlorella sp., while a longer extraction time does not have a favorable impact on the content of phenols in extracts. Moreover, in a study performed by Awaluddin et al . in which proteins and carbohydrates were extracted from C. vulgaris , the authors concluded that higher temperatures (above 160 °C) are needed for efficient extraction.…”
Section: Introductionmentioning
confidence: 99%